Socio-economic and environmental significance of dry land resources of Ethiopia and their development challenges - Lemenih, Mulugeta; Kassa, H. (2010)
Dry land resources have national and global significance. Ethiopia, in particular, is a dry land country whose resources are yet to be managed properly if they are to contribute meaningfully to the country’s socio-economic development and environmental resilience. Using major findings of several on-going and completed studies and field level observations , the paper presents brief descriptions of the major natural resources in the dry lands of Ethiopia in terms of agricultural land, wildlife and ecotourism, water (irrigation potential), range for livestock and wildlife, commercial crop and livestock farming, biofuels plantations, and dry forests. It identified the major challenges to developing these resources as misconceptions surrounding the dry lands, policy related constraints, demographic pressure, climatic variability and change, chronic food insecurity, land degradation, and weakening of traditional institutions. In conclusion, the paper outlines measures that would help in sustainably managing these resources. It specifically suggests the need for developing physical land use plans to designate agricultural lands and conservation areas and building the capacity of local authorities to monitor land use and enforce relevant regulations while encouraging and supporting communities to invest in natural resources management work